USE OF MANUAL STRETCHING TECHNIQUES IN THE MANAGEMENT OF PLANTAR FASCIITIS AMONG PHYSIOTHERAPISTS IN KARACHI: A CROSS-SECTIONAL SURVEY - Devi, Bhain; Akhter, Saeed; Mirza Baig, Aftab Ahmed (Annals of Allied Health Sciences, 2024)
Objective: To determine the use of manual stretching techniques in the management of plantar fasciitis among Physiotherapists in Karachi. Material & Methods: A cross sectional survey study was conducted at Dow University of Health Sciences, Civil Hospital and Jinnah postgraduate medical center. About 153 Physiotherapists filled the self-administered questionnaire after providing informed consent. The self-administered questionnaire was designed to collect data. Results: The most common frequent use of each therapy was hamstring stretch (50 % by 36 physiotherapists i.e. 28.6%), Soleus Stretch (70 % by 33 physiotherapists i.e. 21.6%), Gastrocnemius Stretch (70 % by 30 physiotherapists i.e. 20.0%), Standing Stretch on Wedge (30% by 36 physiotherapists i.e. 26.7%), Hallux Dorsiflexion to Stretch Plantar Fascia (30 % by 49 physiotherapists i.e. 32.7%), Seated Toe Extension Stretch (20 % by 50 physiotherapists i.e. 37.0%), Seated Great Toe Stretch (20 % by 43 physiotherapists i.e. 31.2%) and Prosetch (20 % by 50 physiotherapists i.e. 43.9%). Conclusion: The present study concluded that the cure of plantar fasciitis is to facilitate out non-invasive, conservative methods such as manual stretching which is used as the best initial as well as long term therapy. It has shown better results in improving pain and also in complete recovery according to physiotherapists.